Metaplastic Carcinoma with Chondroid Differentiation Arising in Microglandular Adenosis - Ga-Eon Kim; Nah Ihm Kim; Ji Shin Lee; Min Ho Park (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Microglandular adenosis (MGA) of the breast is a rare, benign proliferative lesion but with a significant rate of associated carcinoma. Herein, we report an unusual case of metaplastic carcinoma with chondroid differentiation associated with typical MGA. Histologically, MGA showed a direct transition to metaplastic carcinoma without an intervening atypical MGA or ductal carcinoma in situ component. The immunohistochemical profile of the metaplastic carcinoma was mostly similar to that of MGA. In both areas, all the epithelial cells were positive for S-100 protein, but negative for estrogen receptor, progesterone receptor, HER2/neu, and epidermal growth factor receptor. An increase in the Ki-67 and p53 labelling index was observed from MGA to invasive carcinoma. To the best of our knowledge, this is the first case of metaplastic carcinoma with chondroid differentiation arising in MGA in Korea. This case supports the hypothesis that a subset of MGA may be a non-obligate morphologic precursor of breast carcinoma, especially the triple-negative subtype.